2005
DOI: 10.1590/s1415-47572005000200012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytogenetic analysis in the species Uroderma magnirostrum and U. bilobatum (cytotype 2n = 42) (Phyllostomidae, Stenodermatinae) in the Brazilian Amazon

Abstract: The genus Uroderma includes two species: U. magnirostrum and U. bilobatum. These species are characterized by their high degree of karyotypic evolution, diverging from most other species of the subfamily Stenodermatinae, which have a lower degree of chromosomic evolution. The present study reports the first banding patterns of U. magnirostrum (G-, C-banding and Ag-NOR) and U. bilobatum (C-banding and Ag-NOR). The chromosomic data in conventional staining of U. magnirostrum (2n = 36, NF = 62) and U. bilobatum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…The Ag-NORs described here for the new karyotype of T. bidens were observed on the smallest pair of acrocentric chromosomes (pair 13). The constitutive heterochromatin found in the pericentromeric region of the chromosomes of T. bidens and in the pericentromeric and interstitial regions of some of the chromosomes of T. saurophila was consistent with the pattern observed in other studies of phyllostomine bats , MORIELLE-VERSUTE et al 1996, SANTOS et al 2001, SILVA et al 2005, BARROS et al 2009, GOMES et al 2010.…”
Section: Inversion?supporting
confidence: 90%
See 1 more Smart Citation
“…The Ag-NORs described here for the new karyotype of T. bidens were observed on the smallest pair of acrocentric chromosomes (pair 13). The constitutive heterochromatin found in the pericentromeric region of the chromosomes of T. bidens and in the pericentromeric and interstitial regions of some of the chromosomes of T. saurophila was consistent with the pattern observed in other studies of phyllostomine bats , MORIELLE-VERSUTE et al 1996, SANTOS et al 2001, SILVA et al 2005, BARROS et al 2009, GOMES et al 2010.…”
Section: Inversion?supporting
confidence: 90%
“…In some genera, however, considerable variation is found in the diploid and fundamental numbers , SILVA et al 2005). The marked diploid number variation found in the Tonatia species is not unique Figure 12.…”
Section: Discussionmentioning
confidence: 99%
“…Most genera of phyllostomid bats have highly conserved karyotypes, but there are extensive karyotypic variations among some genera, which make intergeneric comparison by G-banding almost impossible [ 13 , 41 , 46 , 48 ]. In contrast, it is possible to find chromosomal homeologies in all genera of Phyllostominae, except for Tonatia [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are few cytogenetic studies on bats from Brazilian Amazonia (Rodrigues et al, , 2003Neves et al, 2000;Ribeiro et al, 2003;Silva et al, 2005;Pieczarka et al, 2005). The results of these studies have shown that the Phyllostomidae has a high intrafamiliar karyotypic variation and often new species have been detected fi rst by different karyotypes.…”
Section: Introductionmentioning
confidence: 99%